Efforts To Prevent Anemia Through Education On Worms And Checking Hemoglobin (Hb) Levels Of Students At Cikiwul 1 State Elementary School, Bantar Gebang, Bekasi City, West Java - Diah Lestari; Bagya Mujianto; Dewi Inderiati; Citra Amaniah; Nova Hardianto (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
One of the risk factors for worm infections is low knowledge and environmental sanitation. Elementary school age children are a vulnerable group for experiencing this infection. The Cikiwul 1 Bantar Gebang public elementary school is located in the Bantar Gebang Bekasi waste dump area. Poor school environmental sanitation is a risk factor for the spread of worms and the incidence of nutritional deficiencies and absorption, so that students can suffer from anemia. This community service with the community partnership program (IPKM) science and technology scheme aims to prevent anemia through education about worms and hemoglobin examination of Cikiwul 1 public elementary school students. The target audience is 100 students in grades 5 and 6. The implementation method is through education, providing knowledge about worms, measuring the increase in knowledge through pre-test and post-test. Hemoglobin examination using the biosensor method using Point of Care Testing (POCT), based on the criteria of the World Health Organization, 2001) or clinical practice guiding anemia, 2005. The examination material used is the student's capillary blood. Implementation results were obtained from 100 students who took part in the education, 99 students took the initial knowledge measurement (pre-test), and the measurement of increasing knowledge (post-test). The pre-test result was 69.9, the post-test result was 85.1. There was an increase in knowledge of 15.2%. The results of increasing knowledge for the recognition of worm types were 63%, for the prevention of worms 80%, for the causes of worms 52.5%, for the effects of worms 28.3%, and for the detection of worms 11.1%. The overall prevalence of anemia is still relatively high (22%), with moderate anemia predominant (17%). Boys tend to experience anemia more than girls. Class 6 showed the highest proportion of moderate anemia (19.6%), indicating the potential for continued accumulation of nutritional deficiencies. There were no cases of severe anemia, but 1 in 5 children had Hb levels < 11.5 g/dL, which indicates the need for nutritional intervention and continued health monitoring.